51.4k views
2 votes
Inear equation –3x - y = 27.

User Ohlin
by
5.5k points

1 Answer

4 votes

hello


-3x-y=27

to solve this question we need to plug in the respective values and solve the question.

1.


\begin{gathered} -3x-y=27 \\ x=0 \\ y=? \\ xy=\text{?} \\ \text{put x = 0 in the equation and solve} \\ -3(0)-y=27 \\ 0-y=27 \\ y=-27 \\ \\ \text{put x = 0 and solve for xy} \\ xy=(0)(-27)=0 \\ xy=0 \end{gathered}

2.


\begin{gathered} -3x-y=27 \\ x=1 \\ y=\text{?} \\ xy=\text{?} \\ -3(1)-y=27 \\ -3-y=27 \\ -y=27+3 \\ -y=30 \\ y=-30 \\ \\ xy=\text{?} \\ (1)(-30)=-30 \end{gathered}

3.


\begin{gathered} -3x-y=27 \\ x=\text{?} \\ y=0 \\ xy=\text{?} \\ \text{put y = 0 and solve} \\ -3x-(0)=27 \\ -3x=27 \\ -(3x)/(-3)=(27)/(-3) \\ x=-9 \\ \text{solve for xy } \\ x=-9 \\ y=0 \\ xy=\text{?} \\ xy=(-9)(0)=0 \\ xy=0 \end{gathered}

User Homewrecker
by
5.7k points